Optimization of Surgical Tactics in Non-Neoplastic Diseases of the Left Half of the Colon (Eurasian Medical Research Periodical, 2023)
The authors, in the process of scientific and practical research, optimizing surgical tactics in patients with non-tumor diseases of the left half of the colon when performing reconstructive and restorative surgical interventions, reduced the frequency of postoperative complications associated with surgical intervention in the main group from 9.8 to 1.7%, wound complications - from 7 .4 to 5.2%, general complications - from 6.2 to 1.7%, mortality from 3.7 to 0%, which made it possible to achieve the desired aim of the research.